Implementation of the Ternatenese Language Revitalization Policy as an Identity of North Maluku Culture in Ternate City - Syahril Ibnu; Nurprihatina Hasan; Bahtiar Majid (IKIP PGRI Pontianak, 2022)
This study aims to see how the Ternatenese language revitalization policy is implemented in Ternate City, especially 1). To identify what efforts have been and will be carried out by the Municipal Government of Ternate in revitalizing Ternate Language in Ternate City, and 2). To see how Ternatenese language revitalization occurs through Ternatenese teaching and learning in elementary schools in Ternate City. This study used qualitative research and involved 96 (ninety-six) participants, consisting of three (3) related officials, three (3) community leaders, 15 primary school heads, 15 elementary teachers, and 60 elementary students from four sub-districts in Ternate City. (North Ternate, Central Ternate, South Ternate, and Ternate Island. The research participants were selected by applying the purposive sampling technique. Data were collected through face-to-face interviews and relevant documents. The data were analyzed using thematic analysis. Research findings indicate that some Ternatenese language revitalization programs in Ternate City have been and will be carried out by both relevant agencies and schools with several successes, obstacles, and hopes.